Teknologi Informasi, Sistem Informasi Akuntansi Manajemen, Kesesuaian Tugas dan Kinerja Keuangan - Beni Eko Setiawan; Hernawati; Magdalena Nany (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2023)
The purpose of this study is to empirically prove the significant effect of information technology variables, management accounting information systems and task suitability on the company's financial performance variables. This study is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. The sampling technique in this study used purposive sampling. The samples used in this study were owners and managers as well as employees of the finance department who worked at CV. Citra Warna Pelangi totaling 39 people. The data analysis technique used is multiple linear regression analysis using SPSS 20.0 for Windows.The results of this study indicate that partially and simultaneously information technology, management accounting information systems and task suitability have a significant effect on the company's financial performance. Of the independent variables able to influence the dependent variable only 36.10%, while there are still 63.90% influenced by other factors. So that researchers provide suggestions, in order to expand or add research samples and other variables that are closely related theoretically to the variable of the Company's Financial Performance.